Implementing comprehensive quality standards to develop administrative performance in the Iraqi Athletics Federation - Dr. Diar Fakhur-aldeen (الرياضة المعاصرة)
The research aims to develop the administrative performance of the Iraqi Athletics Federation in the light of the application of comprehensive quality standards, the researcher used the descriptive approach in the survey method to suit the nature of the research, and the researcher chose the research community intentionally from the Iraqi Athletics Federation and the number (60) individuals, as for the research sample They were chosen from the members of the Central Iraqi Federation for Athletics and members of some sub-federations of athletics in the governorates and their number reached (40) individuals and thus represented the sample rate (66%) of the total community, and the researcher used the questionnaire to collect the necessary data The researcher has applied and processed the study data using the (IBM SPSS Statistics 20) statistical program to obtain statistical treatments. The most important results regarding the requirements for implementing the comprehensive quality system in the Iraqi Athletics Federation is: There is a database in the federation that includes adequate information about the federation and the activities and services it provides Activities and events are commensurate with the preparation of practitioners, and what is related to the results of quality standards that can be applied and taken advantage of in developing the administrative performance of the Iraqi Athletics Federation is: There is cooperation between members and employees of the union in completing the work, The members and workers are self-reliant in completing the work, and the researcher recommends the Central Iraqi Athletics Federation, the following: the need to apply the results of this study and work with it in order to benefit from it to develop the administrative performance of the union in light of the application of comprehensive quality standards, an update of the requirements and areas of application Total quality standards in the union periodically, according to the latest developments, spreading the culture of total quality among the members and employees of the union.